UNLOCKING THE POWER OF TOPHONETICS: INDONESIAN EFL LEARNERS' PERCEPTIONS ON PRONUNCIATION ENHANCEMENT THROUGH A PHENOMENOLOGICAL LENS - Yulieta Aura Mustika; Aisyah Hamidiyah; Dhafid Wahyu Utomo (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2023)
The aim of this research conducted at one of the public universities in Banten was to investigate the perception of second-semester students in the English Department regarding the features of the Tophonetics application in improving their pronunciation of fricatives. Employing a phenomenological qualitative research design, the researchers selected five participants through purposive sampling, focusing on students who had experience using Tophonetics and were willing to participate. Data was collected through semi-structured in-depth interviews conducted via online Zoom meetings, utilizing three main open-ended questions to delve deeper into participants' experiences. The obtained data was analyzed using the Stevick-Colaizzi-Kenn technique, as described by Moustakas (1994). The analysis revealed four themes, including positive perception, negative perception, the features of Tophonetics, and the obstacles of using Tophonetics. The findings suggest that students in the English Department perceive Tophonetics positively in terms of improving their pronunciation of fricative sounds, highlighting the potential benefits of integrating this application into language teaching and learning practices.